Democracy - Harrison, Ross (Problems of philosophy (Routledge (Firm)), 1993)
Democracy is today universally considered to be a good thing, yet in history has been frequently criticised. Ross Harrison argues the merits of democracy by tracing its history from the works of Plato, Aristotle, Hobbes, Locke, Rousseau, The American Federalists and Hume, Bentham, the Mills, Hegel and Marx. This historical perspective provides a repertory of specific problems where democracy converges upon the values of liberty, equality, knowledge and welfare. These same values can be used to argue the benefits and demerits of democracy. Any overall assessment must therefore take account of such complexity. Democracy shows us how we may navigate between these moral conflicts, by examining the paradoxes and problems that arise and arguing their resolution.